Causes of payment delays and losses in the construction industry - Ramachandra, T; Rotimi, JOB; Hyde, K (UTS ePress, 2015)
Payment delays and losses persist in the construction industry and continue to be a key concern to industry practitioners. Therefore an exploration of the key causes of payment delays and losses is undertaken in this study with the ultimate objective of seeking mitigating solutions. The study adopted a survey approach using an online questionnaire, administered to practitioners from the New Zealand construction industry, comprising consultants, head contractors and subcontractors. The data obtained was analysed using inferential statistical techniques, including comparing means and factor analysis. Factor analysis enabled clustering of the inter-related causes of payment delays and losses in order to find reduced number of causes. Accordingly, the study found that payment problems mainly relate to contractual issues, financial strength of industry players, disputes, short-comings of payment processes and ‘domino effects’. Among them, the financial strength of critical industry players was considered central to payment problems. The study concludes that any solution to these problems must address these primary causes, as a rational starting point. Thus procuring a feasible form of financial security at the outset of a project, and the pre-qualification of the financial status of critical project participants, were found to be significant in the mitigation of construction payment risks.
Keywords: Payment problems; Causal factors; Factor analysis; Construction; New Zealand